Surgical treatment for chronic pancreatitis: A single‐center retrospective study in Japan. (30th July 2020) - Matsumoto, Ippei; Kamei, Keiko; Murase, Takaaki; Yoshida, Yuta; Kawaguchi, Kohei; Matsumoto, Masataka; Satoi, Shumpei; Takebe, Atsushi; Nakai, Takuya; Takeyama, Yoshifumi
Abstract: Background/Purpose: To determine the short‐ and long‐term results of surgical treatments for chronic pancreatitis (CP) at a high‐volume center in Japan. Methods: The records of 151 consecutive patients undergoing surgery for CP were retrospectively reviewed. Selection of surgical procedures used had been according to the Japanese Clinical Practice Guidelines for CP 2015. Long‐term (≥1 year) follow‐up was performed in 100 patients (median of 37 months). Results: Surgical drainage procedures were performed in 107 patients (Frey operation in 81, longitudinal pancreaticojejunostomy in 26), pancreatic resection in 37 (subtotal stomach‐preserving pancreaticoduodenectomy in 11, distal pancreatectomy in 26), and other procedures in six. The rates of postoperative mortality and morbidity were 1% and 26%, respectively. The rates of complete and partial pain relief were 62% and 37%. The frequency of occurrence of severe morbidity was significantly higher after pancreatic resection than in patients receiving drainage procedures (13% vs 2%, P = .019). The rate of new‐onset diabetes was also significantly higher after resection than drainage (60% vs 25%, P = .017). Conclusions: Surgical treatment for painful chronic pancreatitis can be safe and effective. An optimal procedure should guarantee pain relief and preserve a maximum of pancreatic function. Abstract : Highlight Matsumoto and colleagues retrospectively evaluated the surgical outcomes of 151 patients with chronic pancreatitis at a high‐volume center. Detailed analysis of patient characteristics, indications for surgery, and short‐ and long‐term results revealed that surgical treatment for painful chronic pancreatitis can be safe and effective, relieving pain while preserving maximal pancreatic function.